1992
DOI: 10.1002/jgt.3190160209
|View full text |Cite
|
Sign up to set email alerts
|

Supereulerian graphs: A survey

Abstract: A graph is supereulerian if it has a spanning eulerian subgraph. There is a reduction method to determine whether a graph is supereulerian, and it can also be applied to study other concepts, e.g., hamiltonian line graphs, a certain type of double cycle cover, and the total interval number of a graph. We outline the research on supereulerian graphs, the reduction method and its applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 87 publications
0
87
0
Order By: Relevance
“…The method of the proof is to find a large Eulerian circuit in a subgraph of G and to construct from it a long enough trail in G. A similar problem, finding spanning circuits, has been studied extensively in [1]. In order to keep the article self-contained, we give all propositions with proofs.…”
Section: Theorem 13mentioning
confidence: 99%
“…The method of the proof is to find a large Eulerian circuit in a subgraph of G and to construct from it a long enough trail in G. A similar problem, finding spanning circuits, has been studied extensively in [1]. In order to keep the article self-contained, we give all propositions with proofs.…”
Section: Theorem 13mentioning
confidence: 99%
“…[31] surveyed supereulerian graphs, i.e., graphs containing a connected even factor. Zelinka [153] showed that for every integer r there exists a 2-edge connected graph G, of order n, with no Eulerian subgraph covering more than n/r vertices of G. One important result about supereulerian graphs is the following.…”
Section: Connected [2 K]-factorsmentioning
confidence: 99%
“…Zhang [154], the survey of Lesniak and Oellermann [95] or that of Catlin [31]. 2) If a = 2 and n ≥ 3, δ(G) ≥ max{3,…”
Section: Theorem 20 ([15])mentioning
confidence: 99%
“…Pulleyblank [16] showed that determining if a graph is supereulerian, even when restricted to planar graphs, is NP-complete. For more in the literature on supereulerian graphs, see Catlin's survey [6] and its update by Chen and Lai [11].…”
Section: Introductionmentioning
confidence: 99%